Recent Work in Moral Anthropology - Heim, Maria (Journal of religious ethics, 2014)
This special focus issue brings to the Journal of Religious Ethics fresh considerations of moral anthropology as practiced by four emergent voices within the field. Each of these essays, in varying ways, seeks not only to advance an understanding of ethics in a particular time, place, and context, but to draw our attention to shared aspects of the human condition: its discontinuities and fractures, its practices of perception and attention, its interplays of emotion, intuition, and reason, and its thoroughly intersubjective nature. To learn something of Thai Buddhist life-worlds, contemporary Russian modes of being, or the experience of immorality in today's China, each essay argues in turn, is to gain new insight into ourselves.